Christopher A. Sims (1942–2026): Paradigm-shifting macroeconomist and econometrician - Mikkel Plagborg-Møller; Mark W. Watson (Proceedings of the National Academy of Sciences, 2026)
Christopher A. Sims, who died on March 14, 2026, left behind an indelible mark on macroeconomics and econometrics. His Nobel Prize winning research reshaped the paradigm for empirical macroeconomics, creating a rigorous and flexible framework for inferring the effects of macroeconomic policies. He also made important contributions to time series forecasting, Bayesian econometrics, factor modeling, approximation theory, and models of monetary and fiscal policy. Few academics have had as direct an impact on the work of central banks throughout the world. A frank and generous mentor with numerous students, Chris’s impact extends well beyond his published papers.